Best Practice Pengawas Sekolah Meningkatkan Kompetensi Supervisi Akademik Melalui Pembimbingan dan Pelatihan Bagi Kepala Sekolah Binaan di Kabupaten Kupang Tahun 2017 - Ribka Kekado (Dinasti Review, 2022)
Abstract: The background discussed in this Best Practice report is the low competence of school principals in the target schools in Kupang District, East Nusa Tenggara Province. The research question is